Histocompatibility antigens (HLA) in acute lymphocytic leukemia - Ulukutlu, Lamia; Yazıcı, Hasan; Çam, Halit; Esen, Engin; Özbakır, Fatma (The Turkish Journal of Pediatrics, 1986)
The frequency of HLA A9 is found to be high among 30 Turkish patients with acute lymphoblastic leukemia (47%) when compared to the frequency of the same allele (12%) among 186 healthy controls. Our results do not indicate a “protective” allele among our patients, though in some other studies this has been suggested.